2018
DOI: 10.1159/000493656
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognostic Factors of Primary Splenic Angiosarcoma: A Retrospective Clinical Analysis from China

Abstract: Background/Aims: Primary splenic angiosarcoma is an aggressive malignancy originating from endothelial cells with a particularly poor outcome despite radical therapy. Owing to its extremely low incidence, available data for splenic angiosarcoma are limited. The present study aimed to address this limitation by presenting a thorough retrospective analysis of Chinese primary splenic angiosarcoma patients over a 53-year period (1963-2016). Methods: To determine the characteristics of Chinese primary splenic angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 22 publications
1
24
0
3
Order By: Relevance
“…The diagnosis is challenging and is often made only after splenectomy. More than 300 PSA cases have been described 4. Azevedo et al5 reported the case of a 57-year-old woman previously treated for breast ductal carcinoma, and as far as we know, to date, our case was the first case report of PSA with spontaneous rupture in a patient in Brazil.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…The diagnosis is challenging and is often made only after splenectomy. More than 300 PSA cases have been described 4. Azevedo et al5 reported the case of a 57-year-old woman previously treated for breast ductal carcinoma, and as far as we know, to date, our case was the first case report of PSA with spontaneous rupture in a patient in Brazil.…”
Section: Introductionmentioning
confidence: 57%
“…PSA has been reported in association with environmental or occupational exposure to carcinogens as ionizing radiation (e.g. thorium dioxide), arsenic, vinyl chloride, and chemotherapy for lymphoma, these causal relationships have not been unequivocally substantiated, and most cases occur without identifiable risk factors 4 , 14 , 15. PSA is generally a neoplasm of middle-aged and older people with the mean age at presentation of 50–60 years, but cases in young people and children also have been reported 7 , 16 - 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biing Luen Lee reported male sex was the possible predictor of poor prognosis in AS 10 . However, some research suggested gender appeared no obvious correlation with OS probably due to the limited sample size 11,12 . As displayed in the nomogram, age was also observed as an independent factor.…”
Section: Discussionmentioning
confidence: 99%
“…Del 25% al 69% de los casos se presentan con rotura esplénica. El tratamiento de primera opción es la esplenectomía, pero su pronóstico es casi siempre fatal a los pocos meses del diagnóstico [1][2][3] .…”
Section: Introductionunclassified